Determine Influencing Factors Toward Entrepreneurship Activities In Malaysia Using Bayesian Model Averaging - Boon, Sen (UTeM, 2018)
This research examines the adaption of Bayesian Model Averaging (BMA) to determine the model uncertainty and the significance of the potential factor found to be influencing entrepreneurship activities. The aim of the research to identify the best model factors and the significant relation in between the potential key factors that may drive entrepreneurship activity. Many researchers argue in lacking literature documented on this research which may lead to model uncertainty (SME Corp. Malaysia, 2015, Arin et. al., 2015) where influencing determine what factors to selected among number of potential factor found to conduct the research study. Thus, Bayesian Model Averaging (BMA) is selected based on recent literature by highlighting the benefits of BMA is overcome the model uncertainty issues. In addition, BMA analysis able to identify the variables’ importance and significance influence against the dependent variable. At the end of the research result able to identify and determine the important factor that may bring influence on the entrepreneurship activity.